Effect of Tomato Juice (Lycopersicum esculentum) on Malondialdehyde (MDA) Levels of Rattus norvegicus Testes Exposed to Mosquito Repellent Smoke - Wayan Wariata; I Nyoman Bagus Aji Kresnapati; I Gede Angga Adnyana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Mosquito coil smoke contains reactive oxygen species (ROS) that may induce oxidative stress and increase malondialdehyde (MDA) levels as a marker of lipid peroxidation and cellular damage. Tomato juice contains lycopene, a natural antioxidant that may help reduce oxidative stress from free radicals. This study aimed to evaluate the effect of tomato juice administration on testicular MDA levels in rats exposed to mosquito coil smoke. This laboratory experimental study used a Completely Randomized Design (CRD) involving 20 male Rattus norvegicus rats randomly divided into four groups: negative control, positive control (mosquito coil smoke exposure for 8 hours/day), and two treatment groups receiving smoke exposure combined with tomato juice at doses of 3.81 g/day and 7.62 g/day for 30 days. Testicular MDA levels were measured using the Thiobarbituric Acid Reactive Substances (TBARS) method with a UV-Vis spectrophotometer. Data were analyzed using one-way ANOVA followed by LSD post hoc test with a significance level of p < 0.05. The results showed that the positive control group had the highest testicular MDA levels, whereas administration of tomato juice significantly reduced MDA levels in the treatment groups. The greatest reduction was observed in the group receiving 7.62 g/day of tomato juice, with MDA levels approaching those of the negative control group. In conclusion, exposure to mosquito coil smoke increased testicular MDA levels, while tomato juice administration, particularly at higher doses, reduced oxidative stress-induced lipid peroxidation. These findings suggest that tomato juice has potential as a natural antioxidant against oxidative damage from mosquito coil smoke exposure.